Armory information management system Electronic Warfare Operations Battalion Military Communications Department Royal Thai Armed Forces - Kidkarn, Peeratuch; Pulasetayang, Noppawan; Ritthipakdee, Amarita; Soottitantawat, Somkid (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2020)
Development of an armory information management system. Electronic Warfare Operations Battalion Military Communications Department Royal Thai Armed Forces Arising from the realization of the existing system Which lag work. The information is not current. As well as finding weapon information is not conveniently. Until it causes non-fluency in the operation. Supervisors were unable to quickly check the status of the weapon. Therefore has the concept of developing an armory information management system Electronic Warfare Operations Battalion Military Communications Department Royal Thai Armed Forces. The objective is to develop a productive working style and most effective. Which has scope of work by allowing the staff to record and edit, adjunct, delete weapon information at a glance. The armed personnel of each company can search, widen, remand, And can send weapons to repair. Supervisors can check weapon information in the inventory. There is a system administrator to check the usage of system users. In the development of the armory information management system. Electronic Warfare Operations Battalion have used the MySQL program is a database and use PHP for system development. This project can be developed further information in the future.